Alkyl-methylimidazolium tricyanomethanide ionic liquids under extreme confinement onto nanoporous ceramic membranes - Labropoulos, A.I.; Romanos, G.E.; Kouvelos, E.; P. Falaras; V. Likodimos; Francisco, M.; Kroon, M.C.; Iliev, B.; Adamova, G.; Schubert, T.J.S. (Journal of Physical Chemistry C, 2013)
A method to predict the gas permeability of supported ionic liquid membranes (SILMs) was established, using as input the pore structure characteristics of asymmetric ceramic membrane supports and the physicochemical properties of the bulk ionic liquid (IL) phase. The method was applied to investigate the effect of IL nanoconfinement on the CO2 and N 2 permeability/selectivity properties of novel SILMs developed on nanofiltration (NF) membranes employing for the first time the 1-ethyl-3-methylimidazolium and the 1-butyl-3-methylimidazolium tricyanomethanide ILs as pore modifiers. The selected ILs exhibit low viscosity, which allows for faster gas solvation rates and ease of synthesis/purification that makes them attractive for large-scale production. In parallel, the use of ceramic supports instead of polymeric ones presents the advantage of operation at elevated temperatures and pressures and offers the possibility to study the "real" permeability of the confined IL phase, avoiding additional contributions from the gas diffusion through the surrounding solid matrix. The developed SILMs exhibited enhanced CO2 permeability together with high CO2/N2 separation capacity, though with distinct variations depending on the alkyl chain length of the 1-alkyl-3- methylimidazolium cation. Application of the developed methodology allowed discriminating the contribution of the NF pore structural characteristics on the SILM performance and unveiled the subtle interplay of diverse IL confinement effects on the gas permeability stemming from the specific layering of ion pairs on the nanoporous surface and the phase transition of the IL at room temperature, dictated by small variations of the IL cation size. © 2013 American Chemical Society.
cited By 38